Evaluasi Program Proyek Penguatan Profil Pelajar Pancasila (P5) pada Sekolah Menengah Pertama : Studi Kasus SMP Negeri 2 Pematangsiantar - Ivana Elizabeth Tarigan; Dara Aisyah (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
The Strengthening the Pancasila Student Profile Project (P5) is one of the policies in the Merdeka Curriculum aimed at reinforcing students’ character in line with Pancasila values through project-based learning. This study aims to identify and describe the evaluation of the P5 program implementation at SMP Negeri 2 Pematangsiantar. This research used a qualitative method with a descriptive approach. Data were collected through interviews, observations, documentation, and literature studies. Data were analyzed qualitatively using the Kirkpatrick evaluation model (Reaction, Learning, Behavior, Results).The results of the study show that in the Reaction aspect, students felt happy and enthusiastic about participating in P5, although some found independent learning challenging. In the Learning aspect, there was an increase in knowledge and skills, especially on themes such as local wisdom and entrepreneurship, although intensive guidance was still needed. In the Behavior aspect, values such as cooperation, environmental awareness, and anti-bullying began to be practiced, although behavioral changes were gradual and required continuous reinforcement. In the Results aspect, the program was considered effective in strengthening students’ character in line with the Pancasila Student Profile, but faced challenges such as limited facilities, uneven teacher understanding of P5 methods, and time allocation affecting academic learning. Therefore, continuous evaluation and improvement strategies are needed to ensure the Merdeka Curriculum’s objectives through the P5 Project are optimally achieved.